Socio Economic Importance and Ethnobotanical Potentials of Parkia biglobosa (Jacq.) R.Br. ex G.Don - Aderounmu, Adeboyin Funmi; Falana, Adepeju Rebecca; Oladele, Adekunle Tajudeen (NIU Journal of Humanities, 2020)
Parkia biglobosa (PB) (Jacq.) R.Br. ex G.Don is a multipurpose tree species that has been recognized as potential raw materials for local soup and condiment as well as a very good source of plant protein. This work assessed the socio economic importance and the ethno-botanical potentials of PB among the hawkers in Ode-Olo market, Ibadan North Local Government area of Oyo State, Nigeria. Semi-structured questionnaires were used to obtain relevant information from 109 Locust bean sellers. The demographic distribution of the respondents showed 100% females.  Substantial percentage   (68.81%) of the respondents were above 51years with Primary education (43.12%) as their highest form of education. Most (61.47%) respondents had between 5 and 10 household sizes while 38.53% of them had less than 5. Many parts of PB are used in the treatments of various ailments such as Arterial blood pressure, Asthma, Diabetes, Diarrhoea, Eye defects, Ulcer amongst others. PB provides job opportunities (Traders) which enable them fulfill their family responsibilities to train their wards in schools and taking care of domestic expenses. Plantation establishment of PB for large scale production should be encouraged for the potentials. Keywords: Asthma, Ethno medicine, Locust bean, Nutritional benefits.